Formulation of Exchange Rate Policies in Adjustment Programs. (Occasional Papers; Occasional Paper, 1985)
The role of exchange rate policy in economic adjustment has been widely studied and is the subject of numerous theoretical and empirical papers produced in the Fund and elsewhere.